Perbedaan Sikap Siswa yang diberikan Edukasi Kesehatan Audio Visual tentang Pertolongan Pertama Luka Bakar - Maulidya Ayu Effendi; Rida Darotin; Guruh Wirasakti (Jurnal Riset Media Keperawatan, 2024)
Background: Burns are a major cause of health problems, causing deaths every year. Burns usually occur in children, adolescents, and adults. Burns that occur in adolescents in the school environment are usually caused by fire or hot water. Efforts to improve attitudes about burn first aid include providing audio-visual-based health education. Purpose: The purpose of this study was to determine the differences in attitudes of students who were given audio-visual-based health education about first aid for burns at SMPN 14 Jember. Methods: This quantitative research uses a one group pretest-posttest design approach quasi experimental method. The sampling technique was purposive sampling of 34 subjects conducted in March 2024 for two weeks. The questionnaire sheet is the instrument used for data collection. Univariate analysis for percentage frequency distribution, and bivariate analysis with mc nemar test. Results: The results of the Mc Nemar test analysis showed a value of 0.05, indicating a difference in attitudes before and after being given audio-visual-based health education on burn first aid. Discussion: There are differences in the attitudes of students who are given audio-visual-based health education about burn first aid at SMPN 14 Jember.